Synergistic Antifungal, Allelopatic and Anti-Proliferative Potential of Salvia officinalis L., and Thymus vulgaris L. Essential Oils - Alexa, Ersilia (Molecules, 2018)
The current study aimed to investigate the chemical composition and the synergistic potential of two essential oils (EOs), as obtained from Salvia officinalis L. (SEO), and Thymus vulgaris L. (TEO). The antifungal potential was tested in vitro against Fusarium graminearum (Fg 06_17), the herbicidal effect was studied using weed seeds of Amaranthus retroflexus (ARET), Chenopodium album (CALB), Echinochloa crus-galli (EGAL), but also wheat seeds (WS) of the Lovrin variety and tomato seeds Saint-Pierre of the variety. The GC-MS profile highlights that the mains compounds identified in SEO were: caryophyllene (25.364%), camphene (14.139%), eucalyptol (13.902%), and β-pinene (11.230%), while in TEO, the predominant phytochemicals were: γ-terpinene (68.415%) and p-thymol (24.721%). The results indicated that the tested EOs alone as well as in combination have allelopathic effect against investigated seeds, while the synergistic effect of TEO and SEO in terms of fungal growth was demonstrated at a level of 0.06%. Thyme and sage EOs exhibited in vitro anti-proliferative activity on two melanoma cell lines, namely A375 human melanoma and B164A5 mouse melanoma alone, as well as in combination. SEO was most effective in terms of decreasing the cell viability of murine and human melanoma cell lines when compared to TEO.